Who cares for social image? Interactions between intrinsic motivation and social image concerns - Jana Friedrichsen; Dirk Engelmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We consider the interaction of intrinsic motivation and concerns for social approval in a laboratory experiment. We elicit a proxy for Fairtrade preferences before the experiment. In the experiment, we elicit willingness to pay for conventional and Fairtrade chocolate. Treatments vary whether this can be signalled to other participants. Subjects concerned with social approval should state a higher Fairtrade premium when signalling is possible. We find that this is the case, but interestingly only for participants who are not intrinsically motivated to buy Fairtrade. This has important implications both for crowding out of intrinsic motivation through incentives and for producer choices.
Keywords: D03; C91; H41; 330